Factors influencing no-reflow phenomenon in patients with ST-segment myocardial infarction treated with primary percutaneous coronary intervention - Djenić, Nemanja; Džudović, Boris; Romanović, Radoslav; Ratković, Nenad; Jović, Zoran; Djukić, Boško; Spasić, Marjan; Stojković, Siniša; Obradović, Slobodan (Vojnosanitetski pregled, 2020)
Background/Aim. It is not know which factors influence no-reflow phenomenon after successful primary percutaneous intervention (pPCI) in patients with myocardial infarction with ST elevation (STEMI). The aim of this study was to estimate predictive value of some admission characteristics of patients with STEMI, who underwent pPCI, for the development of no-reflow phenomenon. Worse clinical outcome in patients with no-reflow points to importance of selection and aggressive treatment in a group at high risk. Methods. This was retrospective and partly prospective study which included 491 consecutive patients with STEMI, admitted to a single centre, during the period from 2000 to September 2015, who underwent pPCI. Descriptive characteristics of the patients, presence of classical risk factors for cardiovascular disease, total ischemic time and clinical features at admission were all estimated as predictors for the development of no-reflow phenomenon. No-reflow phenomenon is defined as the presence of thrombolysis in myocardial infarction (TIMI) < 3 coronary flow at the end of the pPCI procedure, or ST-segment resolution by less than 50% in the first hours after the procedure. The significance of the predictive value of some parameters was evaluated by univariate and multivariate regression analysis. In univariate analysis, we used the χ2 test and Mann Whitney and Student’s t-tests. Results. No-reflow phenomenon was detected in 84 (17.1%) patients (criteria used: TIMI < 3 coronary flow) and in 144 (29.3%) patients (criteria used: ST-sement resolution < 50%). Patients older than 75 years [odds ratio (OR) = 2.53; 95% confidence interval (CI) 1.48–4.33; p = 0.001] and those who had Killip class at admission higher than 1 had increased risk to achieve TIMI-3 flow after pPCI. Killip class higher than 1 (OR 1.59; 95% CI 1.23–2.04; p < 0.001), left anterior descendent artery (LAD) as infarct related artery (IRA) and total ischemic time higher than 4 hour were associated with increased risk to failure of rapid ST segment resolution after pPCI. Conclusion. Older age and Killip class were main predictors of TIMI < 3 flow, and Killip class, LAD as IRA and longer total ischemic time were predictors for the failure of rapid ST segment resolution after pPCI.